Cash transfers as a response to COVID-19: A randomized experiment in Kenya - Wyatt Brooks; Kevin Donovan; Terence Johnson; Jackline Oluoch-Aridi (Yale University, Economic Growth Center, 2021)
We deliver one month's average profit to a randomly selected group of female microenterprise owners in the Kenyan slum of Dandora, just preceding with the exponential growth of COVID-19 cases. Firm profit, inventory spending, and food expenditures all increase. The transfers simultaneously cause a re-opening of previously closed businesses. PPE spending and precautionary management practices increase to mitigate this effect, but only among those who perceive COVID-19 as a major health risk. Cash transfers can assist in economic stabilization during a pandemic, but the resulting increase in business activity requires policies to inform and encourage mitigation.
Keywords: J16; O12; 330; COVID-19; cash transfers; microenterprises; women